Overview on population screening for carriers with germline BRCA mutation in China - Lei, Huijun; Zhang, Min; Zhang, Luyao; Hemminki, Kari; Wang, Xiao-jia; Chen, Tianhui (Frontiers in Oncology, 2022)
Carriers with BRCA1/2 germline pathogenic variants are associated with a high risk of breast and ovarian cancers (also pancreatic and prostate cancers). While the spectrum on germline BRCA mutations among the Chinese population shows ethnic specificity, the identification of carriers with germline BRCA mutation before cancer onset is the most effective approach to protect them. This review focused on the current status of BRCA1/2 screening, the surveillance and prevention measures, and discussed the issues and potential impact of BRCA1/2 population screening in China. We conducted literature research on databases PubMed and Google Scholar, as well as Chinese databases CNKI and Wangfang Med Online database (up to 31 March 2022). Latest publications on germline BRCA1/2 prevalence, spectrum, genetic screening as well as carrier counseling, surveillance and prevention were captured where available.While overall 15,256 records were retrieved, 72 publications using germline BRCA1/2 testing were finally retained for further analyses. Germline BRCA1/2 mutations are common in Chinese patients with hereditary breast, ovarian, prostate and pancreatic cancers. Within previous studies, a unique BRCA mutation spectrum in China was revealed. Next-generation sequencing panel was considered as the most common method for BRCA1/2 screening. Regular surveillance and preventive surgeries were tailored to carriers with mutated-BRCA1/2 . We recommend that all Chinese diagnosed with breast, ovarian, pancreatic or prostate cancers and also healthy family members, shall undergo BRCA1/2 gene test to provide risk assessment. Subsequently, timely preventive measures for mutation carriers are recommended after authentic genetic counseling.